Changes of phenolic profile and antioxidant activity during cold storage of functional flavored yogurt supplemented with mulberry pomace. (February 2022) - Du, Huaxin; Wang, Xuping; Yang, Huaigu; Zhu, Fan; Tang, Daobang; Cheng, Jingrong; Liu, Xueming
Abstract: The purpose of this study was to investigate the changes in the main phenolic compounds and in vitro antioxidant activity of functional flavored yogurt supplemented with mulberry pomace (MP) during cold storage. Three anthocyanins (cyanidin-3- O -glucoside, cyanidin-3- O -rutinoside and pelargonidin-3- O -glucoside) and six non-anthocyanin monomeric phenolics (resveratrol, catechol, catechin, rutin, quercitrin and quercetin) were identified in the MP. The MP powder addition significantly and dose-dependently increased the contents of total phenol (TPC), total anthocyanin (TAC) and individual phenolics and DPPH and ABTS free radical scavenging activity of the products. During the cold storage, TPC, TAC and contents of individual phenolics and antioxidant activity of MP-fortified yogurts gradually and significantly increased. Antioxidant activity of MP-fortified yogurts is highly related to TPC/TAC. MP-fortified yogurts exhibited the highest antioxidant activity on the 21st day of storage. The results showed that MP can be used as a natural antioxidant, providing a promising natural ingredient for the production of functional dairy products with improved nutritional value and biological activity. Highlights: Mulberry pomace (MP) is rich in anthocyanin and non-anthocyanin phenolic compounds. Total phenolics and antioxidant activity of yogurt enhanced by the addition of MP. Free phenolics and antioxidant activity increased during cold storage of MP-yogurt.